Morphological differentiation of streptomyces clavuligerus exposed to diverse environmental conditions and its relationship with clavulanic acid biosynthesis (2020)
Clavulanic acid (CA) is a potent inhibitor of class A β-lactamase enzymes produced by Streptomyces clavuligerus (S. clavuligerus) as a defense mechanism. Due to its industrial interest, the process optimization is under continuous investigation. This work aimed at identifying the potential relationship that might exist between S. clavuligerus ATCC 27064 morphology and CA biosynthesis. For this, modified culture conditions such as source, size, and age of inoculum, culture media, and geometry of fermentation flasks were tested. We observed that high density spore suspensions (1 × 107 spores/mL) represent the best inoculum source for S. clavuligerus cell suspension culture. Further, we studied the life cycle of S. clavuligerus in liquid medium, using optic, confocal, and electron microscopy; results allowed us to observe a potential relationship that might exist between the accumulation of CA and the morphology of disperse hyphae. Reactor geometries that increase shear stress promote smaller pellets and a quick disintegration of these in dispersed secondary mycelia, which begins the pseudosporulation process, thus easing CA accumulation. These outcomes greatly contribute to improving the understanding of antibiotic biosynthesis in the Streptomyces genus.